PENGEMBANGAN KREATIVITAS ANAK MELALUI PENDEKATAN SAVI (Somatis, Auditori, Visual, Intelektual) DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Mahmudin, Mahmudin (STOK BINA GUNA MEDAN, 2017)
Physical education is a way to develop the childs motor perceptual abilities that affect the development of childs creativity. The development of childs creativity would be formed if in the learning process, student was given the freedom of expression and exploration. Teacher has an important role in the development of students creativity. Creative teacher will produce student who is creative as well. SAVI approach (somatic, auditory, visual, intellectual) is a learning method that involves the emotions, the whole body, allsenses, and all into  andprivate breadth, respecting other individual learning styles that student learns in different ways. SAVI approach will give freedom to the student so that the learning is more effective in developing studentâs creativity.